Historicizing Mobility: Coyoterismo in the Indigenous Ecuadorian Migration Industry. Issue 1 (March 2018) - Stone-Cadena, Victoria; Álvarez Velasco, Soledad
Based on ethnographic research in the Ecuadorian Highlands, this article puts the mobility, migration, and smuggling practices of Ecuador's indigenous people in historical and contemporary context. The people of Ecuador's Southern Highlands have been on the move for generations, and migration is deeply embedded in the social and cultural landscape. In the rural communities of Cañar, indigenous coyotes are more than facilitators of migration: they are community members operating amid broader structural constraints, which have led to the emergence of specific trends in the facilitation of irregularized migration, yet they are expected to adhere to communal principles of reciprocity and trust. We place indigenous migrant narratives of mobility and identity at the center of our analysis of human smuggling, articulating a counternarrative to that of criminalization prevalent in transnational debates of irregularized migration, national security, and border control.